2018
DOI: 10.17306/j.jard.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Acceptability of Local Rice Brands in Nigeria. Which Marketing Functions Really Matter?

Abstract: With an average annual import bill of USD 300 million,Nigeria is the Africa’s largest rice consuming and importingcountry. This has been attributed to the poor qualityof locally produced rice. Despite huge investments of overUSD 1.65 billion made by government and private sectorsin rice processing over the last six years – which has led todramatic improvements in the quality of local rice brands –the consumers’ preference for imported rice brands persists.Prioritizing the implementation of consumer demand-focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In Malaysia, Abdul Latiff and Ayob (2017), identified consumers' knowledge, perception and attitude as factors influencing consumers' preference and attributed the situation to limited awareness or knowledge on domestic rice availability, and the quality characteristics. Also, in south east Nigeria Iweka & Ederewhevbe (2018) reported that, perceived quality of local rice influences consumers' preference while Obih & Baiyegunhi (2018), in accessing consumers' acceptability of local rice brands in Nigeria, lamented that, Nigeria has become Africa's largest rice importing country due to poor quality of locally produced rice. Okeke, Iheanacho & Obasi (2015) stated that rice attributes such as colour, appearance, taste, stickiness after cooking, cleanliness, swelling capacity, availability and grain shape could trigger consumers' preference for it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, Abdul Latiff and Ayob (2017), identified consumers' knowledge, perception and attitude as factors influencing consumers' preference and attributed the situation to limited awareness or knowledge on domestic rice availability, and the quality characteristics. Also, in south east Nigeria Iweka & Ederewhevbe (2018) reported that, perceived quality of local rice influences consumers' preference while Obih & Baiyegunhi (2018), in accessing consumers' acceptability of local rice brands in Nigeria, lamented that, Nigeria has become Africa's largest rice importing country due to poor quality of locally produced rice. Okeke, Iheanacho & Obasi (2015) stated that rice attributes such as colour, appearance, taste, stickiness after cooking, cleanliness, swelling capacity, availability and grain shape could trigger consumers' preference for it.…”
Section: Introductionmentioning
confidence: 99%
“…The Akwa Ibom state government in 2019 announced that 10,000 of 50kg bags of the Faro-52 type long-grain rice were ready for the market with a view to reducing the price of imported rice. Despite huge investments of over USD 1.65 billion made by the Nigerian government and private sectors in rice processing over the last six years with dramatic improvements in the quality of local rice brands, the consumers' preference for imported rice brands persists (Obih & Baiyegunhi, 2018). The study examined how consumers in Akwa Ibom State perceive the locally produced rice in the state and the level of local rice acceptability by the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is an important crop that has allured several studies in Nigeria. Some studies had focused on adoption of improved rice variety (Awotide et al, 2013); consumption and marketing of rice ( Obih & Baiyegunhi 2018) whilst others focused on resource use efficiency (Goni et al, 2007;Ogundari, 2008) and technical efficiency (Ogundele & Okoruwa, 2006). A review of studies related to agricultural producers' efficiency shows there is a large body of literature dealing with farm level technical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is an important crop that has allured several studies in Nigeria. Some studies had focused on adoption of improved rice variety (Awotide et al 2013); consumption and marketing of rice (Obih and Baiyegunhi 2018) whilst others focused on resource use efficiency (Goni et al 2007;Ogundari 2008) and technical efficiency (Ogundele and Okoruwa 2006). A review of studies related to agricultural producers' efficiency shows there is a large body of literature dealing with farm-level technical efficiency.…”
mentioning
confidence: 99%